Development and demise of a fringing coral reef during Holocene environmental change, eastern Ningaloo Reef, Western Australia - Twiggs, Emily; Collins, Lindsay (Elsevier Science BV, 2010)
Reefs lining the western Exmouth Gulf, located at the northern limit of the 300 km long Ningaloo Reef in Western Australia, represent modern incipient coral reefs and veneers of non-reef-building coral/algal communities on exposed Pleistocene or 'give-up' Holocene reef surfaces. Acquisition of sixteen coresalongside U-series TIMS dates were used to confirm the nature of the Pleistocene foundation andcharacterise Holocene reef development. Three calcretised Pleistocene units were identified as 1) the Last Interglacial (MIS 5e) reef directly underlying Holocene units, 2) a mid-Pleistocene (MIS 7?) bioclastic conglomerate unit, and 3) a Pleistocene alluvial fanglomerate. Eight Holocene reef facies (total thickness of 1.8-5.3 m) included coral framework facies (domal, arborescent, mixed, tabulate and encrusting) and detrital facies (carbonate sand, skeletal rubble and alluvial fan deposits). Holocene ages range from 7.93 to 5.8 ka BP with vertical accretion ranging from 1.46 to 9.88 mm/year (avg. 4.11 mm/year). Highest rates of accretion and thickest accumulation occurred in the most seaward and deepest cores composed of massive coral framestone and coralline algal crusts.A six stage Holocene chronology is proposed, including 1) coastal inundation from 8 to 8.5 ka BP, 2) initiation 'start-up' from 8 to 7.5 ka BP, 3) rapid growth 'catch-up' and back-step from 7.5 to 7 ka BP, 4) rapid aggradational growth 'catch-up' from 7 to 6.5 ka BP, 5) reef decline 'give-up' and detrital buildup from 6.5 to 5.8 ka BP, and 6) detrital buildup and progradation from 5.8 ka BP to present. Changes in reef facies and the ultimate demise of the Holocene reef probably involved a combination of increased sea-level, coastal flooding and erosion during the mid-Holocene highstand, with associated increase in sedimentation, turbidity and decline in water quality; burial by sediment buildup during the mid-Holocene highstand and detrital progradation during the mid- to late-Holocene regression; and, the introduction of alluvial sediment during cyclones and other severe storms to an already stressed community. Modern communities have thus shifted from coral-dominated to bored macroalgal pavements. This study shows that integration of reef development processes with response to environmental change can be used to assess future pressures on coral reef ecosystems globally.